2021
DOI: 10.1186/s12943-021-01428-1
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between cancer-associated fibroblasts and immune cells in the tumor microenvironment: new findings and future perspectives

Abstract: Cancer-associated fibroblasts (CAFs), a stromal cell population with cell-of-origin, phenotypic and functional heterogeneity, are the most essential components of the tumor microenvironment (TME). Through multiple pathways, activated CAFs can promote tumor growth, angiogenesis, invasion and metastasis, along with extracellular matrix (ECM) remodeling and even chemoresistance. Numerous previous studies have confirmed the critical role of the interaction between CAFs and tumor cells in tumorigenesis and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
854
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,165 publications
(870 citation statements)
references
References 365 publications
(408 reference statements)
15
854
0
1
Order By: Relevance
“…High amounts of lactic acid secreted by CAFs with an upregulated expression of MCT4 as an energy substrate are absorbed by cancer cells, and these participate in the metabolic alteration of cancer cells, thereby enhancing tumor malignancy. In the present study, the western blotting results showed that the expression levels of α-SMA and FAP, the two most widely used markers for identifying CAFs ( 41 , 42 ), were upregulated in HIFs after co-culture. Moreover, the results from the immunofluorescence staining experiments confirmed the upregulation of α-SMA and FAP, and a narrower, longer and spindle-shaped morphology of the cells was observed in the induced CAFs that was similar to that commonly exhibited in activated fibroblasts, as one of their characteristic features in CAFs ( 43 ).…”
Section: Discussionsupporting
confidence: 53%
“…High amounts of lactic acid secreted by CAFs with an upregulated expression of MCT4 as an energy substrate are absorbed by cancer cells, and these participate in the metabolic alteration of cancer cells, thereby enhancing tumor malignancy. In the present study, the western blotting results showed that the expression levels of α-SMA and FAP, the two most widely used markers for identifying CAFs ( 41 , 42 ), were upregulated in HIFs after co-culture. Moreover, the results from the immunofluorescence staining experiments confirmed the upregulation of α-SMA and FAP, and a narrower, longer and spindle-shaped morphology of the cells was observed in the induced CAFs that was similar to that commonly exhibited in activated fibroblasts, as one of their characteristic features in CAFs ( 43 ).…”
Section: Discussionsupporting
confidence: 53%
“…They can also be used as a tool for intercellular material and information exchange and as a carrier for intercellular information transmission to transfer information molecules such as DNA, noncoding RNA (including miRNA and long-chain noncoding RNA (lncRNA)), mRNA, and protein. Exosomes are self-regulating, and can also regulate adjacent cells and distant target cells by autocrine or paracrine mechanisms, and mediate the physiological and/or pathological activities of the body [ 42 ]. Exosomes are involved in angiogenesis, EMT, invasion and metastasis, immune escape, drug resistance, and other aspects in the occurrence and development of tumors and have excellent clinical application prospects (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The precise interaction pro le between tumor cells and CAFs are under intensive exploration, where the extracellular vesicles (EVs) serving as crucial cargo carriers of diverse pro-tumor molecules to mediate intercellular communication have received close attention 17,18 . Tumor cell-derived EVs speci cally modify the stromal cellular phenotype and reshape the TME to form a premetastatic niche and support tumor metastasis 19 .…”
Section: Introductionmentioning
confidence: 99%